Results of Laboratory Trials with Eucalyptus hybrid, Wood, Fresh and Afrer Storage for Newsprint - Guha, S. R. D.; Singh, Man Mohan; Bhola, P. P. (Indian Forester, 1975)
Laboratory experiments carried out on the production of newsprint from a furnish containing 30% chemical pulp from Eetta reed (Ochlandra travancorica) and 70% stone ground wood pulp, refiner mechanical pulp or cold soda pulp or hot sulphite pulp from stored and fresh Eucalyptus hybrid (Mysore gum) are described. The results show that newsprint of satisfactory strength properties could be prepared from fresh and stored wood. The power consumption in case of fresh wood is lower than the stored wood in all the cases. Fresh wood gives a brighter and easily bleachable pulp.